Dampak Obyek Wisata Religi Makam Gus Dur Terhadap Pendapatan Pedagang Di Tebuireng Kecamatan Diwek Kabupaten Jombang - Ilyas Nurul Azam (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2019)
This study aims to determine the impact of religious tourism Gus Dur of income traders, these findings are; Visitors to the tomb of Sunan degrees has a goal to enjoy and linger in the pilgrimage, the pilgrims usually they unwind by buying food and drinks around the tomb of Sunan degrees as well as pocket money if there is more they prefer to buy souvenirs bearing the tomb of Gus Dur , even they also provided a place to stay so it can also indirectly increase the income of traders. Friday day on certain days of the Islamic month of Ramadan, especially in the number of visitors increased. Results of analysis of different test average (compare the mean) with t-test with Paired Two Sample for Means (Paired Data) between income trader before he was traded by the trade around the tomb of Gus Dur with an average income of 42 food and beverage vendors, toys children, souvenir, souvenirs and religious equipment moving at intervals 28,444,390,243.90 and 122,250,000,00 with average earnings up to 1,650,000,00 526.097.56 showed that it greatly affects the location of differences on income traders, before trading at the location about the Tomb of Gus Dur by not selling around the grave even though the merchants did not have the homogeneity of old sell.